Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/jpm11080790
|View full text |Cite
|
Sign up to set email alerts
|

Personalized and Self-Management: Systematic Search and Evaluation Quality Factors and User Preference of Drug Reference Apps in Taiwan

Abstract: Background: Drug reference apps promote self-management and improve the efficiency and quality of work for physicians, nurses, pharmacists, and patients. This study aimed to describe a systematic and stepwise process to identify drug reference apps in Taiwan, assess the quality of these apps, and analyze the influential factors for user ratings. Methods: A two-step algorithm (KESS) consisting of keyword growing and systematic search was proposed. Seven independent reviewers were trained to evaluate these apps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 56 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…A study conducted in 2013 on apps to support drug prescribing or provide pharmacology education showed that 68% (208/306) of the apps required payment, with a mean price of £14.25 (US $18.57) per app and a range of £0.62 (US $0.81) to £101.90 (US $132.76) [ 38 ]. The cost of apps also seems to be influenced by the origin of the developer [ 41 ]. In any case, cost is an important determinant in the decision to adopt a mobile health app, regardless of age group and socioeconomic status [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A study conducted in 2013 on apps to support drug prescribing or provide pharmacology education showed that 68% (208/306) of the apps required payment, with a mean price of £14.25 (US $18.57) per app and a range of £0.62 (US $0.81) to £101.90 (US $132.76) [ 38 ]. The cost of apps also seems to be influenced by the origin of the developer [ 41 ]. In any case, cost is an important determinant in the decision to adopt a mobile health app, regardless of age group and socioeconomic status [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of downloads and user ratings probably depend on multiple factors. Navigation, performance, visual appeal, credibility, and quantity of information have recently been identified as the most influential factors on higher user ratings in a study analyzing 23 drug reference apps [ 41 ]. Previous studies have reported highly variable results for the influence of expert involvement in app development on user ratings and the number of downloads [ 18 , 41 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations